2017
DOI: 10.1186/s12888-017-1285-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of ethnicity in pathways to emergency psychiatric services for clients with psychosis

Abstract: BackgroundThis study investigates the role of ethnicity in pathways to emergency mental health care in Toronto for clients with psychosis, while taking into account neighborhood factors. Previous literature has focused on Afro-Caribbean clients, reporting an increased risk of accessing mental health care through negative pathways.MethodsA retrospective chart review for clients from 6 different ethnic origin groups presenting with psychosis – East Asian, South Asian, Black African, Black Caribbean, White Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
4
37
0
1
Order By: Relevance
“…It was agreed that "BAME culture" was not an easily homogenous entity and was instead, complex and multi-layered. 15 However, that is not a reason to ignore the reality of differing cultural needs and expectations. Participants expressed the view that medication effects and side-effects might be more potent for them, leading to poor physical health; their perspective was that they were denied talking therapies and instead had medication prescribed to control them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was agreed that "BAME culture" was not an easily homogenous entity and was instead, complex and multi-layered. 15 However, that is not a reason to ignore the reality of differing cultural needs and expectations. Participants expressed the view that medication effects and side-effects might be more potent for them, leading to poor physical health; their perspective was that they were denied talking therapies and instead had medication prescribed to control them.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report similar issues in many countries where disproportionate numbers of BAME SUs are compulsorily admitted . An investigation of paths to compulsory treatment in Toronto found that BAME groups were more likely to experience admission via mental health law and less likely to engage with treatment . A retrospective chart review was undertaken for SUs with psychosis from 6 different ethnic groups (East Asian, South Asian, Black African, Black Caribbean, White European, and White North American) with a sample size of 765.…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Police are more likely to come into contact with people in mental health crisis who are of lower socioeconomic status and from ethnic minorities (Cloud & Davis 2015;Rotenberg et al 2017). This is particularly important within the New Zealand context where M aori, the indigenous people, are overrepresented in mental health crises and compulsory treatment and present to mental health services with reportedly aggressive behaviour (Mental Health Commission, 2012;Ministry of Health, 2016b;Tapsell & Mellsop 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Mental Health Commission of Canada argues that people from different ethnic groups in Canada have different service needs. These have not been fully examined but are reflected in differences in service use, pathways to care and pathways to emergency services [ 1 4 ]. Differences in exposure to the social determinants of health and specifically psychosocial stressors could underlie differences in need.…”
Section: Introductionmentioning
confidence: 99%